2017
DOI: 10.12944/carj.5.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Varieties and Planting Time on Kharif Onion Production in Lower Shivalik Hills of Himachal Pradesh

Abstract: An experiment was conducted to assess the effect of varieties and planting time on kharif onion production under low hill conditions of Himachal Pradesh at Research Farm of the Institute of Biotechnology and Environmental Science (Dr. Y.S. Parmar, University of Horticulture and Forestry), Neri, Hamirpur for two consecutive seasons (2011 & 2012). The farm is located at an altitude of 620 m above mean sea level with average mean maximum and minimum temperature levels of 31.30 C and 12.40 C, respectively and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Sharma (2009) tested onion varieties bred by different institutes for their performance in the low hills of Himachal Pradesh and revealed that Baswant-780 was the top yielder with a mean bulb production of 230.50 q/ha. As reported by Sharma and Jarial (2017) Agrifound Dark Red was found to be the best suited cultivar for kharif onion production in lower hills of Himachal Pradesh. Sharma and Dogra (2017) evaluated four varieties of onion in kharif season which were planted on five dates separated at 10 days intervals starting from 15 th July to 25 th August and they observed highest bulb yield in variety Agrifound Dark Red transplanted on 15 th August.…”
Section: Standardization Of Suitable Varietymentioning
confidence: 57%
See 2 more Smart Citations
“…Sharma (2009) tested onion varieties bred by different institutes for their performance in the low hills of Himachal Pradesh and revealed that Baswant-780 was the top yielder with a mean bulb production of 230.50 q/ha. As reported by Sharma and Jarial (2017) Agrifound Dark Red was found to be the best suited cultivar for kharif onion production in lower hills of Himachal Pradesh. Sharma and Dogra (2017) evaluated four varieties of onion in kharif season which were planted on five dates separated at 10 days intervals starting from 15 th July to 25 th August and they observed highest bulb yield in variety Agrifound Dark Red transplanted on 15 th August.…”
Section: Standardization Of Suitable Varietymentioning
confidence: 57%
“…However by using scientific techniques like use of high yielding varieties, planting on raised beds, sets planting, making channels to drain irrigation water, using weedicides to control weeds, taking proper plant protection measures farmers can successfully raise kharif onion (Yoo et al 2019;Tripathi and Lawande, 2015;Kandil et al 2013 andLawande et al 2011). Kharif onion production is important in stabilizing onion prices as well as it ensures round the year supply to the consumers (Abd EI-All et al 2012;Sharma and Jarial, 2017). Kharif onion prices are high as compared to rabi crop and hence farmers can earn more benefits by its cultivation (Tripathy et al 2014).…”
Section: Onion Is the Most Important Vegetable Crop Among Variousmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also observed in the current study, wherein lowest neck thickness was noted in Agrifound White (3.66cm). Sharma and Jarial (2017) evaluated different onion varieties and reported a lowest neck thickness in the variety Agrifound Light Red. Similar to the present reports, Mohanta and Mondal (2014) also reported significantly different variations in neck thickness with respect to varieties, planting time and interaction between both.…”
Section: Neck Thicknessmentioning
confidence: 99%
“…The highest average yield was observed in variety FDR. On the other hand, Sharma and Jarial (2017) revealed that there was a significant effect of both varieties and transplanting dates. The highest average yield was observed in cultivar AFDR.…”
mentioning
confidence: 95%